2016
DOI: 10.1051/e3sconf/20160908002
|View full text |Cite
|
Sign up to set email alerts
|

Seismic response of earth dams considering dynamic properties of unsaturated zone

Abstract: Abstract. It is conventionally assumed in the analysis and design of earth dams that the soil located above the phreatic line, i.e. the uppermost seepage flow line, is completely dry. However, there is often an unsaturated flow of water through an unsaturated zone above this borderline and variation in moisture content in this zone results in variation of matric suction throughout this region. Variation of matric suction, in turn, results in variation of effective stresses in this zone. In this research, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…-the study in [41] investigates the displacement and acceleration in the upper part of the earth dam, and the stress state in the body of the dam, with and without considering the water saturation of soil. The calculations were conducted using the FEM and the FLAC program.…”
Section: Introductionmentioning
confidence: 99%
“…-the study in [41] investigates the displacement and acceleration in the upper part of the earth dam, and the stress state in the body of the dam, with and without considering the water saturation of soil. The calculations were conducted using the FEM and the FLAC program.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of unsaturated zones in earth structures such as earth dams considerably influences their seismic and dynamic behavior. [1][2][3] Furthermore, two-thirds of the earth's surface is covered by unsaturated soils, 4,5 and the top unsaturated soil layers influence the site response to the traveling seismic waves, the study of which requires an in-depth knowledge of saturation dependency of unsaturated soil dynamic and cyclic properties. The cyclic behavior of soils and their dynamic properties, such as shear modulus, have been studied substantially for dry and saturated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, software like 1D Plaxis was also used wholly to conduct the required numerical simulation to study and compare of some earth dam's failure after earthquakes [10], while the same software used also in term of 2D analyses in some similar cases [11]. In a related context, it is observed that some recent studies are extended to consider the unsaturated zones within dam body in the seismic response analyses [12].…”
Section: Introductionmentioning
confidence: 99%